Investigation of the antioxidant, anticancer, wound healing, immunomodulatory and dna protective activities of coriandrum sativum and petroselinum crispum / Esther Tang Lai Har - Esther, Tang Lai Har (2014)

(untitled)
Coriandrum sativum L. and Petroselinum crispum (Mill.) Nyman ex A.W. Hill are herbs of the Apiaceae family used as seasoning condiments. Traditionally, the herbs have been used for ailments like diarrhoea, bronchitis, insomnia and haemorrhoids. In this study, the antioxidant, anticancer, wound healing, immunomodulatory and DNA protective activities of C. sativum and P. crispum was evaluated. C. sativum (root, leaf and stem) and P. crispum (leaf and stem) extracts were evaluated for their effect on the proliferation of the breast cancer cell lines, MCF-7 and MDA-MB-231, and the colorectal cancer cell line, HT- 29, using the MTT assay. C. sativum (root) ethyl acetate extract showed the lowest IC50 value (200.0 ± 2.6 μg/mL). The P. crispum dichloromethane extract exhibited the highest phenolic content (42.31 ± 0.50 mg GAE/g) and ferric reducing ability (0.360 ± 0.009 mmol/g) while C. sativum (leaf and stem) aqueous extract displayed the best DPPH radical scavenging activity (IC50 = 1335.0 ± 37.7 μg/mL). The effect of C. sativum (root) ethyl acetate and P. crispum dichloromethane extracts on wound healing, lymphocyte activation, DNA protection and MCF-7 cancer cell migration were investigated. Lymphocytes exposed to H2O2 and pretreated with C. sativum extract (200 μg/mL) showed increased cell viability (115.6 ± 10.6%) compared to the control (86.4 ± 5.5%), thus exhibiting protection against H2O2- induced lymphocyte cytotoxicity. Mouse fibroblasts, 3T3-L1 cells pre-treated with C. sativum or P. crispum extracts (400 μg/mL) indicated 21.5 and 50.9% protection against H2O2-induced DNA damage, respectively. The scratch motility assay showed that C. sativum and P. crispum extracts (300 μg/mL) inhibited MCF-7 cell migration by 94 ± 1 and 41 ± 4%, respectively. As cell migration is necessary for metastasis of cancer cells, Abstract iii inhibition of migration is an indication of protection against metastasis. However, the extracts did not exhibit wound healing properties using the in vitro scratch wound assay. The effects of C. sativum (root) ethyl acetate extract on antioxidant enzymes, caspases and cell cycle of MCF-7 cells was studied. MCF-7 cells treated with C. sativum extract (200 μg/mL) showed increased superoxide dismutase activity and decreased glutathione peroxidase and catalase activities. As superoxide dismutase converts superoxide anion to H2O2, the decrease in H2O2-quenching glutathione peroxidase and catalase results in H2O2 accumulation and possibly, MCF-7 cell death. It is suggested that the C. sativum extract inhibited MCF-7 cells by the death receptor and mitochondrial apoptotic pathways as there were increased expression levels of caspases-3, -8 and -9. Flow cytometric analysis also showed cell cycle arrest at the G2/M phase. HPLC and GC-MS analysis of C. sativum (root) ethyl acetate extract showed the presence of ascorbic acid, p-coumaric acid, cinnamic acid, 4,4,5,7,8-pentamethyl-3,4-2H-isocoumarin-3-one, 1,3,4- tris(trimethylsilyloxy)octadecan-2-amine and L-valine. This study showed that C. sativum and P. crispum had antioxidant, anticancer, immunomodulatory and DNA protective activities and provided scientific evidence supporting the health promoting properties associated with the intake of these herbs in the diet. Addition of these herbs to the daily diet may help strengthen the antioxidant and immune systems of the body and protect from cancer and metastasis.